A combined kinematic and kinetic analysis at the residuum/socket interface of a knee-disarticulation amputee. (November 2017) - Tang, Jinghua; McGrath, Michael; Hale, Nick; Jiang, Liudi; Bader, Dan; Laszczak, Piotr; Moser, David; Zahedi, Saeed
Highlights: Biomechanics at residuum/socket interface were studied via tests on different terrains Interface kinematics were analysed by dynamic coupling using 3D motion capture Interface kinetic stresses were measured at different residuum locations Angular coupling ties up with the temporal pressure changes at proximal regions Axial coupling profile ties up with the longitudinal shear stress profile Abstract: The bespoke interface between a lower limb residuum and a prosthetic socket is critical for an amputee's comfort and overall rehabilitation outcomes. Analysis of interface kinematics and kinetics is important to gain full understanding of the interface biomechanics, which could aid clinical socket fit, rehabilitation and amputee care. This pilot study aims to investigate the dynamic correlation between kinematic movement and kinetic stresses at the interface during walking tests on different terrains. One male, knee disarticulation amputee participated in the study. He was asked to walk on both a level surface and a 5° ramped surface. The movement between the residuum and the socket was evaluated by the angular and axial couplings, based on the outputs from a 3D motion capture system. The corresponding kinetic stresses at anterior-proximal (AP), posterior-proximal (PP) and anterior-distal (AD) locations of the residuum were measured, using individual stress sensors. Approximately 8° of angular coupling and up to 32 mm of axial coupling were measured when walking on different terrains. The direction of the angular coupling shows strong correlation with the pressure difference between the PP and AP sensors. Higher pressure was obtained at the PP location than the AP location during stance phase, associated with the direction of the angular coupling. A strong correlation between axial coupling length, L, and longitudinal shear was also evident at the PP and AD locations i.e. the shortening of L corresponds to the increase of shear in the proximal direction. Although different terrains did not affect these correlations in principle, interface kinematic and kinetic values suggested that gait changes can induce modifications to the interface biomechanics. It is envisaged that the reported techniques could be potentially used to provide combined kinematics and kinetics for the understanding of biomechanics at the residuum/socket interface, which may play an important role in the clinical assessment of prosthetic component settings, including socket fit quality.